Trends in mortality rates associated with multiple myeloma in the United States, 1999–2023 - Jiang, Ye; Liang, Guanghua; Cao, Yongping (Frontiers in Oncology, 2025)
BackgroundDespite substantial therapeutic advances, multiple myeloma (MM) continues to be an important contributor to cancer-related mortality in the United States. Understanding long-term mortality patterns is essential for guiding equitable clinical and public health strategies.MethodsWe used CDC WONDER mortality data from 1999–2023 to evaluate MM-related deaths among U.S. adults aged ≥25 years. Age-adjusted mortality rates (AAMRs) were calculated using direct standardization to the 2000 U.S. population. Temporal trends were examined using Joinpoint regression to estimate annual percent changes (APCs) and identify significant shifts over time. Analyses were stratified by age, sex, race/ethnicity, state, and urbanization level.ResultsNationally, MM mortality declined over the study period. Most age groups younger than 85 years showed statistically significant decreases in AAMR, whereas adults aged ≥85 years experienced a modest increase (APC = +0.67; 95% CI, 0.48–0.86). Males consistently exhibited higher AAMRs than females, although both showed declining trends. Substantial and persistent disparities were observed across racial and ethnic groups, as well as geographic and urbanization categories. Notable state-level heterogeneity was evident, with some states—including New York, Ohio, and Kansas—showing accelerated recent declines in mortality.ConclusionFrom 1999 to 2023, MM-related mortality in the U.S. declined overall, but substantial and persistent disparities remained by age (notably a rising burden among the oldest adults), race/ethnicity, sex, geography, and urbanization. These findings underscore the need for targeted research that links diagnosis, treatment uptake, and outcomes, and for policies to ensure equitable access to proven MM therapies so that survival gains are distributed more uniformly across all population groups.